Difference in Burnout Conditions for Male and Female Employees of Bank Perkreditan Rakyat (BPR) - Teja Kusuma; Afdal Afdal (Jurnal Neo Konseling, 2020)
This research is motivated by the existence of employees who work not optimally because they experience burnout that has an impact on their work. This study aims to describe the different burnout conditions for men and women. This research is in the form of comparative descriptive with a sample of 50 employees. The instrument used was a questionnaire with a Likert slaka model. From the results of the study note that there are significant differences between the burnout of male and female employees.